American Society for Composites 2021 2021
DOI: 10.12783/asc36/35916
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GNP on the Tensile Response of Stitched Composites

Abstract: Through-the-thickness stitching of layered composites provides through-the- thickness reinforcement to enhance the interlaminar tensile and shear strengths while maintaining structural continuity. However, under planar mechanical loads, stitched composites develop strain concentrations in the resin rich areas around the stitch seam causing a local reduction in mechanical properties. In this study, nanographene toughened epoxy is used to reduce strain concentrations around stitch seams and increase the global t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Alaziz et al studied the influence of GNP toughening on the tensile response of stitched composites. 85 The tensile modulus and strain energy density were improved by 9.71% and 7.18%, respectively, by the presence of 1 wt% GNP in the modified epoxy. Strain concentrations around stitching sites were significantly reduced, indicating increased energy absorption in those zones under axial deformations.…”
Section: Methods To Reduce Permeabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Alaziz et al studied the influence of GNP toughening on the tensile response of stitched composites. 85 The tensile modulus and strain energy density were improved by 9.71% and 7.18%, respectively, by the presence of 1 wt% GNP in the modified epoxy. Strain concentrations around stitching sites were significantly reduced, indicating increased energy absorption in those zones under axial deformations.…”
Section: Methods To Reduce Permeabilitymentioning
confidence: 94%
“…Alaziz et al studied the influence of stitching patterns on the tensile response of composites and concluded that the resin rich areas around the stitches form zones of stress concentrations that altered the local properties of these composites. 84,85 With a CTE mismatch between the stitching thread and the resin pocket around it, micro-cracks initiate from these zones that run through the thickness of the specimen along the stitching thread. 35,36 Such crack networks influence the gas permeability of composites and, therefore, need to be reduced to increase the fuel containment performance of composite cryogenic tanks.
Figure 6.Cracks initiating from resin columns around through-the-thickness stitches in cryogenically cycled stitched composites.
…”
Section: Permeability and Transverse Microcrackingmentioning
confidence: 99%